Analysis of Fire and Smoke Spread in Ki Hajar Dewantara Auditorium, State University of Jakarta, Using Fire Dynamics Simulator - Arrizq, Ariq Harits; Setyadi, Pratomo (Universitas Negeri Malang, 2023)
Fire behavior and smoke spread are influenced by various factors, including the amount and condition of combustible material, ventilation openings, and ceiling height. A high amount of combustible material in the auditorium poses a significant fire hazard, hence, efforts need to be made to minimize the risk. One approach is to use Computational Fluid Dynamic software, such as Fire Dynamics Simulator (FDS), to model fire combustion. In this research, it provides an overview of the heat release rate (HRR) of fires that occur as well as the effect of differences in ceiling height and the effect of ventilation on fire spread. This research employed Polyurethane foam, commonly used for auditorium seats, as the sample material. Furthermore, it modeled two fire points, one on the 9th floor and the other on the 10th floor, in the middle of seat rows. The development of fire in the modeling was described by the results of visualization, HRR, burning rate, and temperature rise. These results provided insight into the speed at which fire and smoke spread. The starting point on the 9th floor had the highest flame spread rate due to the ceiling jet phenomenon, where a high amount of combustible material caused the ceiling temperature to increase, producing a heat flux that could burn surrounding seats. In both scenarios, the smoke spread rapidly toward the ventilation openings. However, it was denser on the 9th floor as the starting point was farther from the ventilation openings, and the smoke on the 10th floor was less dense.